Factors associated with domestic violence against women in primary care in Brazil: An integrative review - Santiago, Glaucia Helena de Paula (Seven Editora, 2024)
Introduction: Domestic violence against women is a serious complex problem that brings different health problems, the identification of factors associated with this violence enables a better follow-up of women Objective: To carry out an integrative review to identify the factors associated with domestic violence in women treated in primary health care in Brazil. Methods: Searches were conducted in the databases of the VHL Regional Portal, SciELO, Capes Portal and PubMed. Inclusion criteria were: studies with epidemiological designs (cohort, case-control and cross-sectional) that used instruments validated in Brazil to measure violence and addressed the issue of domestic violence against women treated in primary care. Results: The most frequent types of domestic violence, respectively, were: psychological violence (53.8%), physical violence (46.1%) and sexual violence (13.6%). Different factors were associated with violence, such as low schooling, low family income, having witnessed or suffered aggression in the family of origin,  and alcohol use by the partner. Conclusion: knowledge of the factors associated with domestic violence that occurs in a territory with primary health care coverage enables the development of programs that meet women's needs in the integrality. DOI:https://doi.org/10.56238/sevened2024.007-021